Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jve.2021.100041
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in Uganda: Identification of infected blood donors for micro-elimination

Abstract: Background The drive to eliminate viral hepatitis by 2030 is underway. However, locally generated data on active infection is required to focus such efforts. We performed a regionally-inclusive survey to determine prevalence of active HCV, genotypes and related factors among Ugandan blood donors. Methods Participants from regional blood banks and blood collection centers were surveyed for information on demographic, clinical and lifestyle factors. Blood was assayed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our study tested for HBsAg, but not hepatitis C virus (HCV), based on our prior finding of zero prevalence in 81 PWH starting ART in Uganda, but 4% (3/76) prevalence of HBsAg. Although low HCV prevalence was confirmed in one study [29], others have found higher prevalence [30,31], thus we may have failed to identify this possible source of ALT or AST elevations.…”
Section: Discussionmentioning
confidence: 74%
“…Our study tested for HBsAg, but not hepatitis C virus (HCV), based on our prior finding of zero prevalence in 81 PWH starting ART in Uganda, but 4% (3/76) prevalence of HBsAg. Although low HCV prevalence was confirmed in one study [29], others have found higher prevalence [30,31], thus we may have failed to identify this possible source of ALT or AST elevations.…”
Section: Discussionmentioning
confidence: 74%
“…3 Based on other studies, the prevalence of HbsAg positivity amongst pregnant women in Northern Uganda is close to 10%, 35 with active Hepatitis C infection present in 2%–8% of the population. 36,37 Of note, the Niamey Protocol helps to distinguish patterns of liver morbidity due to schistosomiasis from other etiologies, ameliorating this concern somewhat. Further, relatively few children had abnormal ultrasound findings, limiting the power of the study to detect associations, as evidenced by the wide confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Uganda like any other sub-Saharan African country has a functional infrastructure and service delivery system for HIV care except for HBV [ 16 ]. As of now, both HIV and HBV patients are managed in separate clinics with separate staff teams even though they all receive antiretroviral treatment.…”
Section: Introductionmentioning
confidence: 99%